The Primitive and Imprimitive Soluble Subgroups of GL(4,Pk) - Razzagh, Behnam (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper we will determined all of the primitive and imprimitive Soluble Subgroups of GL(4,pk). It turns out that the number of types of the irreducible Soluble Subgroups in GL(4,pk)are 10 types and are Mi,i=1,…,10. moreover we find these subgroups.